Functional response and mutual interference of Diaeretiella rapae (Hymenoptera: Aphidiidae) on Brevicoryne brassicae (Homoptera: Aphididae) - Fathipour, Yaghoub; Hosseini, Ali; Talebi, Ali; Moharramipour, Saeid (Entomologica Fennica, 2006)
Functional response and mutual interference are the most important behavioural characteristics that reveal different aspects of host–parasitoid interactions. In this study, functional response and mutual interference of the parasitoid wasp, Diaeretiella rapae (M’Intosh) attacking the cabbage aphid, Brevicoryne brassicae (Linnaeus) were investigated. Logistic regression was used to distinguish the shape of the functional response (type II or III). Nonlinear least-square regression was used to estimate the attack rate (a) and handling time (Th). Nicholson’s model and linear regression were used to determine per capita searching efficiency and interference coefficient, respectively. Logistic regression suggested a type II response on B. brassicae nymphs. The per capita parasitism decreased significantly from 80.80 (67.33%) to 11.85 (9.88%) as parasitoid densities increased from 1 to 8 females. Consequently, the per capita searching efficiency decreased significantly from 1.173 to 0.205 as parasitoid densities increased from 1 to 8. The rate of parasitism increased as the host density increased from 2 to 50, and subsequently the parasitoid density decreased from 8 to 1. Therefore, different host–parasitoid ratios could affect the efficacy of D. rapae.